A Performance of Baffled Stirred Tank Reactor in Map Mineral Recovery - Luluk Edahwati; Sutiyono; Suprihatin (BIOMEJ, 2024)
In the agricultural and wastewater treatment industries, the formation of Magnesium Ammonium Phosphate (MAP), also known as struvite, is an important process to utilize organic waste and produce value-added phosphate fertilizers. In this context, the use of a stirred tank reactor equipped with baffles is a major concern. This study aims to evaluate the performance of a stirred tank reactor with baffles in the recovery of MAP. Analysis of the experimental results shows that the use of baffles has a significant impact on process efficiency and the quality of the MAP product produced. This study provides a deeper understanding of the role of baffles in maintaining the flow pattern and mixing of raw materials in the reactor tank, thus making an important contribution to the development of more efficient and environmentally friendly phosphate fertilizer manufacturing technology. best phosphate obtained 27%, ph 10, temperature 30oC and molar ratio 1:1:2 Keywords: molar ratio, pH, precipitation, RTB, temperature, struvite